Effect of β,γ-CHF and β,γ-CHCl dGTP halogen atom stereochemistry on the transition state of DNA polymerase β() - Oertell, Keriann (2012)
Recently, we synthesized the first individual β,γ-CHX dGTP diastereomers ((R)- or (S)-CHX; X = F or Cl), and determined their structures in ternary complexes with pol β. We now report stereospecificity by pol β on the mixed β,γ-CHX diastereomer pairs using NMR and on the separate diastereomers using transient kinetics. For both the F and Cl diastereomers, the R isomer is favored over the S isomer for G•C correct incorporation, with stereospecificities [(k(pol)/K(d))(R)/(k(pol)/K(d))(S)] of 3.8 and 6.3 respectively and also for G•T misincorporation, with stereospecificities of 11 and 7.8 respectively. Stereopreference for the (R)-CHF dGTP diastereomer was abolished for k(pol) but not K(d) with mutant pol β (R183A). These compounds constitute a new class of stereochemical probes for active site interactions involving halogen atoms. As Arg183 is unique in family X pols, design of CXY deoxyribonucleotide analogues to enhance interaction is a possible strategy to inhibit BER selectively in cancer cells.